Drought analysis based on grid-rainfall data - Hear, Xin Jie (Nanyang Technological University, 2020)
Drought analysis is crucial to provide early warning system that tracks, assesses and delivers relevant information of climate, as well as hydrology and water supply conditions and trends. Drought Indices (DIs) are commonly used in drought analysis studies. There are also many different types of precipitation products being used in calculations of DIs. This report proposes utilizing daily gridded rainfall data, APHRODITE monsoon Asia Precipitation dataset (APHRO_MA v1101), and MATLAB programming software, as an alternative way to analyze, identify and quantify drought events. By using this drought analysis method to study the region of Singapore and Southern part of Malaysia (longitude:103.125-104.125⁰E, latitude: 1.125-2.125⁰N), the following information can be extracted out: from 2003 to 2007, the average length of dry spell was generally low, typically lasted ≤ 3 days. Year 2005 saw the most and longest dry spells (72 dry spells and 30 days respectively), and thus the most prone to drought events. Average number of dry spells throughout the region from 2003-2007 was also relatively consistent. It can also be concluded that the study region was overall not prone to drought from 2003-2007. This is in line with the fact that the study region lies near the equator and has a tropical climate, where rainfall is typically relatively abundant all year round.